2001
DOI: 10.1111/0038-4941.00055
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mandatory Seat Belt Laws on Motor Vehicle Fatalities in the United States

Abstract: Objective. This article assesses the effectiveness of mandated seat belt usage. The theory of offsetting behavior asserts that when drivers feel safer, they compensate by driving less cautiously. As a consequence, any lifesaving effects from mandated safety devices such as seat belts could be significantly diminished or entirely offset. Method. This article uses regression analysis and two years (1988 and 1997) of state-level data to test for the presence of offsetting behavior by estimating models explaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Consistent with other studies (Wagenaar 1984;McCarthy 2000;Hu et al 1998;Calkins and Zlatoper 2001;Scuffhan 2003, we find a significant relationship between VMT and crashes. We could not reject the hypothesis that there is a proportional relationship between VMT and total, fatal, serious injury, and materials crashes.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with other studies (Wagenaar 1984;McCarthy 2000;Hu et al 1998;Calkins and Zlatoper 2001;Scuffhan 2003, we find a significant relationship between VMT and crashes. We could not reject the hypothesis that there is a proportional relationship between VMT and total, fatal, serious injury, and materials crashes.…”
Section: Resultssupporting
confidence: 92%
“…The majority of these tests have found evidence of offsetting behavior. But they have been conducted using aggregate data at either the national (Peltzman, 1975;Crandall et al, 1986;Chirinko and Harper, Jr., 1993;Yun, 2002), state (Calkins and Zlatoper, 2001;Cohen and Einav, 2003), county (Keeler, 1994), or city (Dee, 1998;McCarthy, 1999) level. A few researchers have used less aggregated data derived from state police accident reports (Traynor, 1993;Peterson, Hoffer, and Millner, 1995;Harless and Hoffer, 2003).…”
mentioning
confidence: 99%
“…Similarly, Houston, Richardson, and Neeley (1995), Sen (2001), and Young and Likens (2000) found that traffic fatalities in general benefit from the enactment of seat belt laws. Conversely, evidence of offsetting behaviors has been found by Garbacz (1990), and Sen and Mizzen (2007), who show a positive relationship between seat belt use and nonoccupant death rates, as well as by Calkins and Zlatoper (2001) and Risa (1994) who show evidence of a positive relationship between occupant and non-occupant fatalities and seat belt use. Some investigations, such as Garbacz (1992) and Derrig, Segui-Gomez, Abtahi, and Liu (2002), even find no relationship at all between seat belt use and traffic fatalities.…”
Section: The Offset Hypothesis and The 'Peltzman Effect'mentioning
confidence: 99%